Cooperative and synchronized rotation in motorized porous frameworks: impact on local and global transport properties of confined fluids. (2nd November 2020) - Evans, Jack D.; Krause, Simon; Feringa, Ben L.
Abstract : Simulations reveal the influence of rotating molecular motors and the importance of orientation and directionality for altering the transport properties of fluids. This has outlined that motors with specific rotation can generate directed diffusion. Abstract : Molecules in gas and liquid states, as well as in solution, exhibit significant and random Brownian motion. Molecules in the solid-state, although strongly immobilized, can still exhibit significant intramolecular dynamics. However, in most framework materials, these intramolecular dynamics are driven by temperature, and therefore are neither controlled nor spatially or temporarily aligned. In recent years, several examples of molecular machines that allow for a stimuli-responsive control of dynamical motion, such as rotation, have been reported. In this contribution, we investigate the local and global properties of a Lennard-Jones (LJ) fluid surrounding a molecular motor and consider the influence of cooperative and non-directional rotation for a molecular motor-containing pore system. This study uses classical molecular dynamics simulations to describe a minimal model, which was developed to resemble known molecular motors. The properties of an LJ liquid surrounding an isolated molecular motor remain mostly unaffected by the introduced rotation. We then considered an arrangement of motors within a one-dimensional pore. Changes in diffusivity for pore sizes approaching the length of the rotor were observed, resulting from rotation of the motors. We also considered the influence of cooperative motor directionality on the directional transport properties of this confined fluid. Importantly, we discovered that specific unidirectional rotation of altitudinal motors can produce directed diffusion. This study provides an essential insight into molecular machine-containing frameworks, highlighting the specific structural arrangements that can produce directional mass transport.